A New Physical Mechanism of Rainfall Facilitation to New Particle Formation - Suping Zhao; Ye Yu; Jianjun He; Longxiang Dong; Shaofeng Qi (Geophysical Research Letters, 2024)
Abstract Newly formed particles and their growth contribute significantly to cloud condensation nuclei. However, the effect of rain on new particle formation (NPF) is poorly understood. Rainfall removes the pre‐existing large particles by below‐cloud scavenging to reduce condensation and coagulation sinks by 4.0 × 10−2 and 1.5 × 10−4 s−1. The scavenging effect largely depends on the amount and duration of rain and the surface area concentration of the raindrops. NPF events can be facilitated by a combination of fewer condensation sinks and favorable meteorological conditions, contributing 3%–47% of PM2.5 (particulate matter smaller than 2.5 μm). The physical mechanism was confirmed by theoretical analysis. The results help elucidate the NPF process from a physical perspective, which can improve the prediction of the occurrence and duration of haze events. Until precursors are reduced, significant reductions in particulate matter (PM) may be difficult because NPF and its growth recharge the atmosphere with PM.